COMPARISON OF CROATIAN AND EUROPEAN STANDARDS FOR DETERMINING THE FROST SUSCEPTIBILITY OF HYDRAULICALLY BOUND MIXTURES (Advances in Civil and Architectural Engineering, 2021)
The base layer of a multi-layered pavement structure is often a cement-bound material, which combines an aggregate with cement binder. This load-bearing layer is quite rigid, which improves pavement properties, including frost resistance, and extends the life cycle of the pavement. In geographic areas with low temperatures and significant ground water, the bearing capacity of pavement structures can be reduced by volume deformations from freezing and thawing. Cold winters and frost-susceptible soil are present in eastern Croatia and in the city of Osijek. Thus, in this paper we examine the frost susceptibility of cement-bound aggregates, made with materials commonly used in Croatia, in accordance with the current Croatian standard HRN U.B1.050 and a new European standard EN 13286-54. The test mixtures did not meet the conditions for frost-resistant materials. To meet these conditions, one must use a higher cement ratio or a cement with a higher strength class.